2020
DOI: 10.1515/geo-2020-0210
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and land use in the North of Russia: Case study of Karelia and Yakutia

Abstract: Despite harsh climate, agriculture on the northern margins of Russia still remains the backbone of food security. Historically, in both regions studied in this article – the Republic of Karelia and the Republic of Sakha (Yakutia) – agricultural activities as dairy farming and even cropping were well adapted to local conditions including traditional activities such as horse breeding typical for Yakutia. Using three different sources of information – official statistics, expert interviews, and field observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…(Karelian Russian woman born in 1968), underlining that wild food plays a major role in the Karelian diet. Second, Naumov et al (48) reported that in Russian Karelia cattle breeding is currently highly subsidized and the subsidies may help pay for veterinary services that were well-developed during Soviet times (9), thus abandoning existing ethnoveterinary knowledge.…”
Section: Possible Erosive Trajectories Of Ethnoveterinary Knowledge In Karelia Setomaa and Dzukijamentioning
confidence: 99%
“…(Karelian Russian woman born in 1968), underlining that wild food plays a major role in the Karelian diet. Second, Naumov et al (48) reported that in Russian Karelia cattle breeding is currently highly subsidized and the subsidies may help pay for veterinary services that were well-developed during Soviet times (9), thus abandoning existing ethnoveterinary knowledge.…”
Section: Possible Erosive Trajectories Of Ethnoveterinary Knowledge In Karelia Setomaa and Dzukijamentioning
confidence: 99%
“…In most countries, governmental support plays a crucial role in the implementation of the state agri-food policy [14]. The creation of a favorable investment climate and governmental support for concessional lending to agrarian entities should become the economic basis for the reproduction of resources.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is assumed that the Sakha (Yakut) people are descended from a common ancestral population from the Lake Baikal region, genetically and culturally close to Mongols and Buryats until they were displaced by the latter [43]. The northward migration can be explained by the arrival of horse-breeding peoples from the Asian steppes at the beginning of the rst millennium BC, at a time when reindeer breeding ourished in the Eastern Sayan region [42,45]. Thus, the high percentage of lactase de ciency in Siberian populations, in addition to the genetic component, can be explained by the following factors: big practice in milk fermentation practices (the lactose content of mare's milk is 1.5 times higher than of cow's one [46]); later domestication and the presence of admixture with steppe herders have been suggested as possible explanations.…”
Section: Discussionmentioning
confidence: 99%